Respuesta :

Answer:

the answer is false.

Step-by-step explanation:

Answer:

The given statement :

[tex]\sin (-x)=-\cos x[/tex] is a False statement.

Step-by-step explanation:

We are given a statement as:

               [tex]\sin (-x)=-\cos x[/tex] for all the values of x.

But this expression is not correct.

for example if we take x=0

then we have:

[tex]\sin (0)=-\cos (0)\\\\i.e.\\\\0=-1[/tex]

which is incorrect.

Also, when [tex]x=\dfrac{\pi}{2}[/tex]

we have:

[tex]\sin (-\dfrac{\pi}{2})=-\cos (\dfrac{\pi}{2})\\\\i.e.\\\\-\sin (\dfrac{\pi}{2})=-\cos (\dfrac{\pi}{2})\\\\i.e.\\\\-1=0[/tex]

which is again a false identity.

Hence, we get that the given statement is False.

ACCESS MORE